2018
DOI: 10.1111/ijac.13093
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐free sealing glass for sodium‐beta alumina battery

Abstract: A CaO‐Bi2O3‐Al2O3‐B2O3 glass system was studied as a sealant for sodium‐sulfur battery. The thermal properties such as thermal expansion coefficient, glass transition, and softening temperature were determined by dilatometry and differential scanning calorimetry. Selected glasses, based on the thermal properties, were bonded with α‐alumina substrate followed by aging in air at 400°C for 100 hours and in sodium vapor at 350°C for 100 hours. The interfacial compatibility and resistance to sodium vapor corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, glass contains leachable elements such as calcium, which can diffuse into the β -alumina electrolyte and increase its resistivity [191]. Recently, a few studies reported the advantages of Bi-doped sealing glass [194,195]. The incorporation of bismuth oxide in the glass composition increases the thermal expansion coefficient and decreases the glass transition temperature.…”
Section: Cell Sealingmentioning
confidence: 99%
“…On the other hand, glass contains leachable elements such as calcium, which can diffuse into the β -alumina electrolyte and increase its resistivity [191]. Recently, a few studies reported the advantages of Bi-doped sealing glass [194,195]. The incorporation of bismuth oxide in the glass composition increases the thermal expansion coefficient and decreases the glass transition temperature.…”
Section: Cell Sealingmentioning
confidence: 99%